Employment impacts of industrial transformation in China: A case study of Yangtze River Delta - Hu, Zijiang; Zhang, Xiao; Yue, Chen; Huang, Yiye; Sun, Ling; Huo, Yang (Frontiers in Sustainable Food Systems, 2023)
The United Nations formally adopted 17 sustainable development goals (SDGs) at the summit in 2015. With the goal of SDGs, China has formulated the “3,060” dual carbon target, that is, to achieve a carbon peak before 2030 and carbon neutrality before 2060. Consequently, this goal will direct positive changes in industrial transformation, and employment quality will be impacted. In this article, 106 listed manufacturing enterprises in the Yangtze River Delta are selected to explore the impacts of industrial transformation and just transition on employment. The result shows that the industrial transformation has no significant promoting effect on employment quality in state-owned enterprises (SOEs), and just transition has no significant moderating effect. However, in private enterprises, industrial transformation has a significant negative impact on employment equality. Moreover, employee training can alleviate the negative impact of industrial transformation on employment quality. On the contrary, employee welfare will play a negative moderating role. The conclusions of this research can help enterprises make better strategies to guarantee the interests of employees and stimulate staff. In addition, the government should advise relevant enterprises to transform steadily.